An Ecosystem Model of Islamic Character Development: A Qualitative Case Study of Integrated Religious Strategies in a Rural Indonesian Madrasah - Ali, Moch. Yusron; Sajudin, Muhammad; Syaiful, Muhammad (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study aims to develop an ecosystem model of Islamic character development by examining how integrated religious strategies operate within a rural Indonesian madrasah. It specifically investigates how affective role modeling, Islamic-based reinforcement, and contextual value integration interact to shape students’ moral and spiritual formation. The study addresses a gap in the existing literature, which often treats religious programs as isolated activities rather than as interconnected institutional systems. A qualitative single case study design was employed at MTs Diponegoro Japah in Blora Regency, Central Java. Data were collected through prolonged school observations, semi-structured interviews with seven key informants, and document analysis of institutional records. Thematic analysis was conducted to identify patterns across data sources, supported by triangulation and member checking to ensure credibility and trustworthiness. The findings indicate that Islamic character development functions as a dynamic ecosystem composed of three mutually reinforcing pillars: affective teacher–student relationships, structured but gradually internalized reward mechanisms, and the integration of moral values into authentic daily contexts. These strategies collectively foster sustained behavioral improvement despite socio-economic and infrastructural constraints. The novelty of this study lies in conceptualizing religious character education as an institutional ecosystem rather than a set of discrete programs. The study contributes theoretically by refining models of Islamic character formation and practically by offering context-sensitive guidance for rural madrasahs seeking sustainable and adaptive character education strategies.